Increased Frequency of Dysfunctional Siglec-7−CD57+PD-1+ Natural Killer Cells in Patients With Non-alcoholic Fatty Liver Disease - Sakamoto, Yuzuru; Yoshio, Sachiyo; Doi, Hiroyoshi; Mori, Taizo; Matsuda, Michitaka; Kawai, Hironari; Shimagaki, Tomonari; Yoshikawa, Shiori; Aoki, Yoshihiko; Osawa, Yosuke; Yoshida, Yuji; Arai, Taeang; et al. (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is a progressive disorder that can develop into liver fibrosis and hepatocellular carcinoma. Natural killer (NK) cells have been shown to protect against liver fibrosis and tumorigenesis, suggesting that they may also play a role in the pathogenesis of NAFLD. Sialic acid-binding immunoglobulin-like lectins (Siglecs) are a family of inhibitory and activating receptors expressed by many cell types, including NK cells. Here, we investigated the phenotypic profiles of peripheral blood and intrahepatic NK cells, including expression of Siglecs and immune checkpoint molecules, and their association with NK cell function in patients with NAFLD. Immune cells in the peripheral blood of 42 patients with biopsy-proven NAFLD and 13 healthy volunteers (HVs) were identified by mass cytometry. The function of various NK cell subpopulations was assessed by flow cytometric detection of intracellular IFN-γ and CD107a/LAMP-1, a degranulation marker, after in vitro stimulation. We found that peripheral blood from NAFLD patients, regardless of fibrosis stage, contained significantly fewer total CD56+ NK cell and CD56dim NK cell populations compared with HVs, and the CD56dim cells from NAFLD patients were functionally impaired. Among the Siglecs examined, NK cells predominantly expressed Siglec-7 and Siglec-9, and both the expression levels of Siglec-7 and Siglec-9 on NK cells and the frequencies of Siglec-7+CD56dim NK cells were reduced in NAFLD patients. Notably, Siglec-7 levels on CD56dim NK cells were inversely correlated with PD-1, CD57, and ILT2 levels and positively correlated with NKp30 and NKp46 levels. Further subtyping of NK cells identified a highly dysfunctional Siglec-7−CD57+PD-1+CD56dim NK cell subset that was increased in patients with NAFLD, even those with mild liver fibrosis. Intrahepatic NK cells from NAFLD patients expressed elevated levels of NKG2D and CD69, suggesting a more activated phenotype than normal liver NK cells. These data identify a close association between NK cell function and expression of Siglec-7, CD57, and PD-1 that could potentially be therapeutically targeted in NAFLD.